Connection Loneliness and Emotion Regulation with Quarter Life Crisis in Adolescents in Gresik - Lingga Kusuma wardani; Heri Saputro; Wiwik Widiyawati (Journal Of Nursing Practice, 2025)
Background: Teenagers are often described as agents of change who certainly have their own challenges and needs. This means that people who have reached adulthood must be ready to face the social world. If a person feels unable to cope with the changes and challenges that arise, they may develop negative reactions or emotional crises within themselves. Quarter life crisis is what people experience in response to instability, distrust, fear of failure, isolation, constant change, multiple choices, and also fear of impotence. Purpose: The aim of this research is to reveal the relationship between Loneliness (X1) and emotion regulation (X2) with the quarter life crisis (Y) in Adolescents in Gresik. Methods: This research is a quantitative study with a cross-sectional approach. This is done to test a predetermined hypothesis. This research uses a cross-sectional study, which means that data on the independent and dependent variables are each collected and observed only once . There were 468 populations and researchers involved 215 students of the Faculty of Health, Muhammadiyah University of Gresik, the sample was obtained randomly. Results: There is no relationship between loneliness and emotion regulation with quarter life crisis. And no p-value results were obtained in the statistical test of the correlation of Emotion Regulation with Quarter Life Crisis and a p-value of 0.5 (>0.05) was obtained, which means there is no relationship between loneliness and quarter life crisis. Conclusion: There is no relationship between loneliness and emotion regulation with quarter-life crisis. The occurrence of quarter-life crisis can be due to external factors such as work, social pressure, or changes in lifestyle, not just individual psychological factors.